Water absorption, anti-shrink efficiency and decay resistance of treated wood by silica based solutions - Dizman Tomak, Eylem; Şam Parmak, Ebru Devrim; Arpacı, Şebnem Sevil (Yildiz Technical University, 2020)
In this study, the effect of two different silica (SiO2) based solutions on water absorption, anti-shrink efficiency and decay resistance of Scots pine wood was studied. Sol-gel process was used in order to prepare SiO2 based solutions. One of the SiO2 based solutions (Sol-gel 1) was prepared by using tetraethoxysilane (TEOS) and de-ionized water (TEOS:H2O=1:1/2). The same precursors was used for preparing the other solution (Sol-gel 2) but with a different molar ratio of TEOS:H2O=1:4. Scots pine wood specimens were first vacuum impregnated with the solutions and then cured. The level of water absorption and anti-shrink efficiency were determined with cyclical wetting tests, total of 14 days. Specimens were exposed to brown rot fungus, Coniophora puteana attack according to modified EN 113 standard to determine the best SiO2 based solution for sufficient decay resistance. Leached specimens were also suspected to decay test in order to evaluate any loss in effectiveness in decay resistance due to possibility of silica leaching. Both solutions had similar weight percent gains in wood, around 25%. SiO2 treated specimens decreased water absorption of wood as 20% in comparison with un-treated controls. Anti-shrink efficiency of wood was found as 26% for Sol-gel 1 solution and 35% for Sol-gel 2 solution at the end of the test. Decay resistance of treated specimens was in the range of 63-91% in comparison with controls. Sol-gel 2 solution were found efficacious in suppressing Coniophora puteana attack when no leaching prior the decay test was used, however, Sol-gel 1 solution seemed to be ineffective against fungus attack that exhibited more than 3% weight loss. Leached specimens had higher weight loss than un-leached specimens. The silica in leached wood supposed to be not sufficient to prevent brown rot fungus attack on wood. Results clearly showed that Sol-gel 2 solution had better water absorption and anti-shrink efficiency rates, and decay resistance than Sol-gel 1 solution.
Keywords: Scots pine; sol-gel; decay resistance; anti-shrink efficiency; water absorption